2022
DOI: 10.1155/2022/6232264
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical Efficacy of Huangkui Capsule plus Methylprednisolone in the Treatment of Nephropathy and the Effect on Urinary Protein and Serum Inflammatory Factors in Patients

Abstract: Objective. The study aimed to assess the clinical efficacy of Huangkui capsule plus methylprednisolone in the treatment of nephropathy and the effect on urinary protein and serum inflammatory factors in patients. Methods. Between June 2017 and July 2020, 90 patients with nephropathy admitted to our hospital were recruited after assessment of eligibility and assigned via the random number table method (1 : 1) to receive either methylprednisolone tablets (observation group) or methylprednisolone tablets plus Hua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%